Conservation strategy based on soil erodibility with several land covers and slopes in the upstream of Air Bengkulu Watershed - Vinni Lovita; Bambang Sulistyo (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2025)
Global land cover changes driven by increasing demand for agricultural, residential, and industrial land have caused various environmental issues, including soil erosion. The study aimed to analyze soil erodibility values upstream of the Air Bengkulu watershed based on land cover and slope factors. The analysis was conducted using soil samples obtained through purposive sampling based on soil map units, topography, and land cover. Soil erodibility values were determined through laboratory analysis of organic matter, texture, structure, and soil permeability, followed by calculating erodibility. After obtaining the distribution of erodibility values, the next step involves identifying erodibility values based on slope and land cover to analyze the interaction between slope and land cover on erodibility values. Conservation recommendations are provided based on slope, land cover and consideration of community aspects to reduce erodibility values and minimize erosion risk. Results indicate that soil erodibility in the Air Bengkulu watershed ranges from very low to very high, with most areas classified as low. The findings suggest that soil erodibility values vary depending on land cover and slope. Higher erodibility values were observed in areas with minimal land cover, especially in mining and cultivated land with poor management practices. In contrast, dense vegetation such as forests and well-maintained plantations significantly reduced soil erodibility values. The interaction between slope and land cover plays a crucial role in determining soil susceptibility to erosion risk. Vegetative and mechanical conservation strategies are suggested to mitigate erosion risks, improve land productivity, and support ecosystem sustainability in the region.